Comparison of two pharmacokinetic–pharmacodynamic models of rocuronium bromide during profound neuromuscular block: analysis of estimated and measured post-tetanic count effect. (March 2022) - Couto, Mafalda; Vide, Sérgio; Marco-Ariño, Nicolás; Troconiz, Iñaki F.; Esteves, Simão; Nunes, Catarina S.; Amorim, Pedro; Mendes, Joaquim
Abstract: Background: Profound neuromuscular block (NMB) is important in surgeries where complete immobility is considered essential to improve tracheal intubation and surgical conditions. Rocuronium bromide is a commonly used NMB agent. This work describes a noninvasive approach for estimation of post-tetanic count (PTC) based on two pharmacokinetic (PK) models, the Saldien and the De Haes models. The aim was to investigate the rocuronium bromide PK–pharmacodynamic (PD) relationship in estimating the PTC effect during profound NMB. Methods: In this prospective, non-randomised, observational study, an induction bolus of rocuronium bromide was administered followed by continuous infusion for maintenance of a PTC of 1-2. measured every 3 min. Measurements were analysed as discrete categorical data and by applying the nonlinear mixed-effect modelling approach. Performance of the selected models was evaluated through simulation model-based diagnostics, further assessing the precision of the parameter estimates and the performance of the models at the individual level. Results: Data from 30 adult patients undergoing elective abdominal or neurosurgical procedures were included. Post-tetanic count response profiles during rocuronium bromide infusion were successfully characterised using the population PD analysis. The models showed a good performance for all PTC categories, albeit with a moderate over-prediction of PTC >6. Conclusions: Our findings indicate that using plasma concentrations of rocuronium bromide estimated with either of the two models, combined with a PD model, provides equal model performance when predicting PTC. These promising results may provide an important advance in guiding rocuronium bromide administration when profound NMB in routine clinical practice is desired.